Neons Fashion LLP (B) : The Setbacks - Mukherjee, Saral; Abhishek; Balasubramani, Soundarya (London : Indian Institute of Management, Ahmedabad, 2019)
This case describes the events after the Bangalore Fashion Week that ultimately led to the closure of business.
Originally Published InMukherjee, S., Abhishek., & Balasubramani, S. (2019). Neons Fashion LLP (B): The Setbacks. IIMA/MAR0509(A). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business failures -- Case studies; Fashion show -- India -- Bangalore -- Case studies